2016
DOI: 10.3389/fonc.2016.00034
|View full text |Cite
|
Sign up to set email alerts
|

Che-1/AATF: A Critical Cofactor for Both Wild-Type- and Mutant-p53 Proteins

Abstract: The p53 protein is a key player in a wide range of protein networks that allow the state of “good health” of the cell. Not surprisingly, mutations of the TP53 gene are one of the most common alterations associated to cancer cells. Mutated forms of p53 (mtp53) not only lose the ability to protect the integrity of the genetic heritage of the cell but also acquire pro-oncogenic functions, behaving like dangerous accelerators of transformation and tumor progression. In recent years, many studies focused on investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…In agreement with previous findings [9,30], we found that Che-1 inhibition not only strongly affects BCP-ALL cell growth, implying that it could be involved in leukemia clonal expansion, but also sensitizes BCP-ALL cells to chemotherapeutic treatment. The main function known of Che-1 is to activate gene transcription [31]. RNA-seq experiments in NALM-6 and in a primary BCP-ALL cell line confirmed this role, highlighting how this protein is required for control in the expression of several genes involved in cell growth.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In agreement with previous findings [9,30], we found that Che-1 inhibition not only strongly affects BCP-ALL cell growth, implying that it could be involved in leukemia clonal expansion, but also sensitizes BCP-ALL cells to chemotherapeutic treatment. The main function known of Che-1 is to activate gene transcription [31]. RNA-seq experiments in NALM-6 and in a primary BCP-ALL cell line confirmed this role, highlighting how this protein is required for control in the expression of several genes involved in cell growth.…”
Section: Discussionmentioning
confidence: 85%
“…The main function known of Che‐1 is to activate gene transcription . RNA‐seq experiments in NALM‐6 and in a primary BCP‐ALL cell line confirmed this role, highlighting how this protein is required for control in the expression of several genes involved in cell growth.…”
Section: Discussionmentioning
confidence: 86%
“…AATF has been linked to p53-mediated stress response (8). Consequently, to exclude indirect effects of AATF depletion on ribosome biogenesis via its link to the p53 pathway, we also compared the effects of AATF siRNA treatment in p53 wild-type and p53 −/− HCT116 cell lines (26).…”
Section: Resultsmentioning
confidence: 99%
“…In its function as RNA polymerase II-specific transcription factor, AATF has been previously suggested to bind the promoter region of the TP53 gene, modulating the transcriptional activity of p53 protein and regulating cellular stress responses (58). Importantly, we show that the function of AATF in ribosome synthesis is independent of p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation